Financial Literacy. Who, whom and what are they Training for? Comparative Analysis 2016–2020 - Németh, Erzsébet; Vargha, Bálint Tamás; Domokos, Kinga (Public Finance Quarterly, 2020)
The research assessed whether progress has been made in the education and development of financial awareness in Hungary since 2016. We reviewed the changes in the state’s role in the development of financial literacy, and in a questionnaire survey we examined what kind of organizations, who and in what topics are involved in trainings outside the public education. It was found that between 2016 and 2020, there was an increasing focus on developing the financial literacy, while the vast majority of the trainings continues to target the most easily reachable school age group. The National Core Curriculum identified economic and financial education as a goal for schools. However, outside of vocational high schools, such knowledge is not taught as a compulsory subject. In 2017, the Government adopted a strategy to improve the financial awareness of the population, and the first accredited financial literacy textbooks were published. The results of non-public education organisations show that the number of training programs and their participants has tripled. The average duration of trainings has become longer, multi-day trainings mainly for adults appeared. Knowledge transfer continued to focus on individual frugality and financial awareness, financial self-knowledge, attitude, and behaviour. The education of investment and entrepreneurship knowledge still isn’t a priority. Most of the trainings do not take into account the income situation and social background of the target groups and do not pay attention to the development of financially vulnerable groups.